FRI0157 EPSTEIN BARR VIRUS BLOOD REPLICATION INCREASES DURING ACTIVE SYSTEMIC LUPUS ERYTHEMATOSUS. (13th June 2020) - Breillat, P.; Mathian, A.; Burrel, S.; Hié, M.; Fadlallah, J.; Pineton de Chambrun, M.; Cohen, F.; Boutolleau, D.; Rozenberg, F.; Calvez, V.; Amoura, Z.
Abstract : Background: A role for Epstein Barr Virus (EBV) infection in Systemic Lupus Erythematosus (SLE) pathogenesis is highly suspected. The frequency of EBV seroprevalence and DNA detection in peripheral blood mononuclear cells are increased in SLE patients compared to healthy controls. Objectives: To analyse the relationship between EBV blood replication and SLE disease activity. Methods: Monocentric, observational and retrospective study of SLE patients (ACR or SLICC criteria) who have had a blood EBV DNA assessment using Polymerase Chain Reaction (artus® EBV Virus QS-RGQ assay) between 2012 and 2018. Exclusion criteria were: organ or bone marrow transplant, absence of EBV seroconversion and insufficient data. SLE clinical features, the Safety of Estrogens in Lupus Erythematosus National Assessment–Systemic Lupus Erythematosus Disease Activity Index (SELENA-SLEDAI) flare index (SFI) and therapeutic regimen on the day of EBV DNA load assessment were recorded. A SELENA-SLEDAI score > 4 defined an active SLE. A blood EBV DNA load ≥125 IU/mL was defined as elevated. Results: A total of 105 patients (98 women and 7 men) were included in the study. At inclusion, median (quartiles) age and SLE duration were 34 (23.5-43) and 7 (2-14) years old, respectively. Treatment were hydroxychloroquine (HCQ) (n = 67; 64%), prednisone (n = 66; 63%) with an average (±Standard Deviation) dose of 11.3 (±16) mg/day and an immunosuppressant (n = 42; 40%). According to SFI, 57 SLE patients were experiencing a flare at the time of EBV assessment; flares were classified as severe and mild/moderate in 38 (36%) and 19 (18%) SLE patients, respectively. According to the SELENA-SLEDAI score, 60 patients (57%) were deemed active and 45 (43%) inactive. Main clinical manifestations were arthritis in 32 (30%) patients, constitutional symptoms (fever, weight loss, anorexia or lymphadenopathy) in 31 (30%), cutaneous involvement in 23 (22%), glomerulonephritis in 19 (18%), cytopenia in 14 (13%), neuropsychiatric involvement in 13 (12%) and serositis in 10 (16%). Blood EBV DNA was elevated in 54 (90%) of the 60 patients with active lupus versus 6 (13%) of the 45 patients with inactive SLE (p <10 -4 ). It was increased in 34 (89%) of the 38 patients with severe flare, in 17 (89%) of the 19 patients with a mild/moderate flare (p = 1) and in 8 (17%) of the 48 patients without flare (p <10 -4 vs severe flare and p <10 -4 vs mild/moderate flare). EBV DNA load correlated with SELENA-SLEDAI score (r=0.58; p<0.0001). Elevated blood EBV DNA was not associated with HCQ, prednisone or immunosuppressant intakes. Eighteen patients with active SLE had a second assessment of blood EBV DNA load. For these patients, the median [range] of viral load was significantly higher during periods of active SLE (236 [0-2680] IU/mL) compared with periods with lower SELENA-SLEDAI score (0 [0-1537] IU/mL, p<10 -4 in paired analysis). Conclusion: Blood EBV viral load is dramatically increased in active phase of SLE, independently of the treatment. We were unable to demonstrate whether the replication of EBV was the cause or the consequence or just an epiphenomenon of the disease activity. Further studies are needed to study whether EBV viral load is linked with Interferons secretion or B lymphocyte activation. Disclosure of Interests: None declared